2021
DOI: 10.3390/cells10092475
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Promotes the Survival of Adipose Mesenchymal Stem/Stromal Cells and Enhances Their Therapeutic Effects in Cisplatin-Induced Liver Injury via Modulating TGF-β1/Smad and PI3K/AKT Signaling Pathways

Abstract: Autophagy is a key metabolic process where cells can recycle its proteins and organelles to regenerate its own cellular building blocks. Chemotherapy is indispensable for cancer treatment but associated with various side-effects, including organ damage. Stem cell-based therapy is a promising approach for reducing chemotherapeutic side effects, however, one of its main culprits is the poor survival of transplanted stem cells in damaged tissues. Here, we aimed to test the effects of activating autophagy in adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 87 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…In the current study, stem cell groups showed more meaningful upregulation in SDF1α expression than the control and DOX groups. This was also observed by El Nashar et al [56], Akcora et al [57], and Du et al [58]. Moreover, BMSCs preconditioned with HA showed the highest SDF1α level among all treated groups, suggesting the role of HA in enhancing cell migration.…”
Section: Discussionsupporting
confidence: 79%
“…In the current study, stem cell groups showed more meaningful upregulation in SDF1α expression than the control and DOX groups. This was also observed by El Nashar et al [56], Akcora et al [57], and Du et al [58]. Moreover, BMSCs preconditioned with HA showed the highest SDF1α level among all treated groups, suggesting the role of HA in enhancing cell migration.…”
Section: Discussionsupporting
confidence: 79%
“…In Choi et al's (2019) study, pretreatment with necroptotic inhibitor, Necrostatin-1 markedly suppressed CP-induced auditory cell death, while the treatment of apoptosis inhibitor, ZVAD did not. Likewise, the protective effect of the autophagy pathway was also reported in CP-induced damage to the liver cells (Qu et al, 2019;Nashar et al, 2021), and cochlear cells (Fang and Xiao, 2014;Yang Q. et al, 2018;Liu et al, 2019;Pang et al, 2019). More Interestingly, trehalose which alleviated CP-induced AKI by activating autophagy (Zhu et al, 2020), recently, its pro-autophagic activity has made it also a potential treatment for CP-induced ototoxicity (Li et al, 2022b).…”
Section: Impact Of Autophagy Activation and Necroptosis Inhibition On...mentioning
confidence: 89%
“…Besides the NRF2 signal pathway, some groups also have reported LQ-induced promiscuous activation of multiple pathways in the liver. For example, LQ treatment improves liver fibrosis via regulating TGF-β1/Smad and Hippo/YAP pathways, and both TGF-β1/Smad and Hippo/YAP pathways are related with liver injury. , In addition, LQ is also considered as an AMPK activator and enhances the phosphorylation of AMPK in hepatocytes, which confers to the therapeutic action of LQ against oxidative hepatic injury and mitochondrial dysfunction . Moreover, cyclophosphamide-induced liver sinusoidal endothelial injury and inflammatory injury can be alleviated by LQ treatment via regulating the TLR4-NFκB signal pathway .…”
Section: Discussionmentioning
confidence: 99%